Impact of 2011 Resident Duty Hour Requirements on Neurology Residency Programs and Departments. (July 2014) - George, Benjamin P.; Probasco, John C.; Dorsey, E. Ray; Venkatesan, Arun
Objective: In 2011, the Accreditation Council on Graduate Medical Education (ACGME) redefined resident duty hour requirements by reducing in-hospital duty hour requirements for residents in an effort to improve patient care, resident well-being, and resident education. We sought to determine the cost of adoption based on changes made by neurology residency programs and departments due to these requirements. Methods: We surveyed department chairs or residency program directors at 123 ACGME-accredited US adult neurology training programs on programmatic changes and resident expansion, hiring practices, and development of new computer-based resources in direct response to the 2011 ACGME duty hour requirements. Using data from publicly available resources, we estimated respondents' financial cost of adoption. Results: In all, 63 responded (51% response rate); 76% were program directors. The most common changes implemented by programs were adding night float systems (n = 31; 49%) and increasing faculty responsibility (n = 26; 41%). In direct response to the requirements, 21 programs applied to ACGME for 40 additional residents, 29 of which were fully covered by institutional funds. In direct response to the requirements, nearly half of the departments (n = 26) hired individuals for a total of 80 hires (or 64 full-time equivalents), most commonly mid-level practitioners. The total estimated cost to responding departments was US 12.7 million or US 201, 000 per department annually. When projecting expenses of planned changes for the following year, costs increased to US 360, 000 per department, with 5-year costs exceeding US 1 million. Conclusions: The most recent restriction on resident duty hours comes at substantial cost to neurology departments and residency programs.